A Practical Study on Promoting the Action of People’s Livelihood and Border Security Project in Guangxi under the Perspective of Border Security–Taking Jingxi City and Longzhou County as Examples - Zhiling Zeng (Journal of Frontier in Economic and Management Research, 2025)
The report of the 20th CPC National Congress emphasizes the maintenance of national security and social stability, and the promotion of prosperity and development of border areas. In order to deeply implement the spirit of the 20th CPC National Congress and actively respond to the state’s call to strengthen borderland governance and promote the improvement of people’s livelihood, this paper conducts a field research on the practice and effectiveness of the livelihood and peace border project in Guangxi’s Jingxi City and Longzhou County, which in turn summarizes the successful experiences of the two areas in infrastructure construction, public service system construction, economic development and social governance, and also finds an imbalance in resource allocation and policy priorities, At the same time, it has also identified the problems of unbalanced resource allocation and policy priority, grass-roots governance capacity to be strengthened, social security system still needs to be improved, and policy implementation and supervision face challenges, and put forward targeted improvement measures such as balancing resource allocation and policy priority, optimizing the public service system, upgrading the capacity of border governance, and strengthening the supervision and implementation of the policy, which has further deepened the understanding of the role of the Livelihoods and Security Border Project in promoting the stability of the borders and the development of the society, and condensed the insights of it on the construction of security of borders. security construction. Finally, it summarizes the successful experience of the implementation of the Livelihood Security Border Project in Jingxi City and Longzhou County found in this research and its implications for the long-term governance and security of the borderlands, and looks forward to the future direction of promoting the development of the Livelihood Security Border Project in Guangxi’s border areas.